Biomarkers and risk factors for the early prediction of immune-related adverse events: a review. Issue 1 (31st January 2022) - Zhang, Ying; Zhang, Xiaoling; Li, Weiling; Du, Yunyi; Hu, Wenqing; Zhao, Jun
ABSTRACT: In recent years, immunotherapy has been widely used to treat patients with malignant tumors. While immune checkpoint inhibitors (ICIs) significantly improve the prognosis of cancer patients, the incidence of immune-related adverse events (irAEs) is increasing. Not only can irAEs accumulate in multiple organ systems throughout the body, but rare adverse reactions may also occur continuously. In severe cases, irAEs can be life-threatening or even lead to death. Therefore, the early identification, diagnosis and treatment of irAEs are very important. Early identification of patients with high-risk irAEs as well as the reduction or avoidance of severe irAEs have important clinical significance. This article will review the research progress of early predictive biomarkers and risk factors for the occurrence of irAEs and propose potential future directions for follow-up research and clinical applications.